FENOMENA MEMANCING KESEDIHAN DI MEDIA SOSIAL (SADFISHING) PADA LITERASI DIGITAL REMAJA - Hamzah, Radja Erland; Putri, Citra Eka (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The phenomenon of sadfishing has created a new trend for social media users in Indonesia, where each user seems to have an urge to show his sadness in order to attract sympathy from many people on social media. The act of sadfishing has an impact on the mental health of the perpetrators, including children and adolescents. Lots of Sadfishing content seems to be a common reaction for someone who is going through a difficult time or pretending to be having a difficult time to get viral on social media. This study aims to explain how to digital literacy for social media users can change public opinion in limiting themselves from the sadfishing phenomenon on social media. The type of research used is descriptive qualitative, with a case study method and data collection techniques by interviewing several high school students and university students in Jakarta. The results of the study found that the audience is in the position of The Dominant-Hegemonic Position or the audience is in a position to accept that digital literacy is able to educate and change the opinions of social media users, especially among teenagers to avoid the phenomenon of provoking sadness on social media.